1993
DOI: 10.1016/0165-4896(93)90024-d
|View full text |Cite
|
Sign up to set email alerts
|

The bankruptcy problem: a cooperative bargaining approach

Abstract: We associate each bankruptcy problem with a bargaining problem and derive old allocation rules for the former by applying well known bargaining solutions to the latter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(60 citation statements)
references
References 9 publications
2
53
0
Order By: Relevance
“…For simplicity, let = f . The next result is parallel to one obtained by Dagan and Volij (1993) in a di¤erent framework. 9 Proposition 3.1 The -asymmetric Nash solution for = f induces the additive CSF (5).…”
Section: ' Classical'bargainingsupporting
confidence: 60%
See 2 more Smart Citations
“…For simplicity, let = f . The next result is parallel to one obtained by Dagan and Volij (1993) in a di¤erent framework. 9 Proposition 3.1 The -asymmetric Nash solution for = f induces the additive CSF (5).…”
Section: ' Classical'bargainingsupporting
confidence: 60%
“…The analysis exploits the observation that these problems are mathematically related -but not equivalent -to the problem of assigning win probabilities in contests. A main result here follows Dagan and Volij (1993) and shows that the class of contest success functions given in (5) can be understood as the weighted Nash bargaining solution where e¤orts represent the weights of the agents. We turn then to the framework of bargaining with claims (Chun and Thomson (1992)) to incorporate explicitly the contestants'e¤orts in the description of the problem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It turns out that well known claims rules can, in this fashion, be described by classical bargaining solutions. For instance, if we apply the Nash bargaining solution [6], we observe that (i) it provides the same allocation when applied to the problem pSpE, cq, dq, and when applied directly to the conflicting claims problem pE, cq; and (ii) it coincides with the constrained equal awards rule [7]. Nevertheless, in general bargaining solutions do not coincide when applied to problems pSpE, cq, dq and pE, cq.…”
Section: Introductionmentioning
confidence: 92%
“…Theorem 2.3 can be seen as a generalization of Dagan and Volij (1993) who showed that the constrained equal award rule for bankruptcy problems corresponds to the Nash bargaining solution of an appropriately chosen bargaining problem.…”
Section: So By Case 1 We Have Xs -Argmax{r[;esy;~y E X(es't)} and Mmentioning
confidence: 99%